The Arab Springs and the “Walk to Work” Movement in Uganda: Contest for Political Space and Freedom. - Ojambo , Robert (African Journal of Education,Science and Technology (AJEST), 2016)
This paper presents an overview of how the Arab Springs influenced events in the Walk-to Work Protests in Uganda during the period after the 2011 election. It builds on the previous analysis of the nexus between the Arab Spring and other conflicts that sprung in different parts of Africa to provide an overview of in the fight for political space in the sub-Saharan Africa with a specific focus on Uganda. The main argument is that the recent Arab uprising have led to significant changes that call for rethinking of critical issues in the study of social movement which has in turn led to enormous implication in the theories of revolution especially in the Arab world. This study employed a qualitative methodology using historical approach to investigate the ‘Walk-to-Work’ protests in Uganda in the larger study of impact of the Arab Springs in the Arab North. Employing the Resource Mobilisation, Political Opportunity Structural and Framing Theories, the study establishes that the Arab Springs influenced a lot of events in the ‘Walk-to-Work’ Protests in Uganda. Our argument here is also that despite the fact that the ‘Walk-to-Work’ protests did not lead to change of Government, they were not mere protests but instead a manifestation of a peaceful struggle for political space in Uganda that has made a big paradigm shift in the politics of this country.